(untitled) (Scientific Journal of Research Studies in Future Management, 2023)
although the results of the research on identifying the factors of creating educational equity and equal access to individuals , the positive effects of this phenomenon are revealed and the educational systems are moving toward this side ; however , there are several obstacles to realization . in this regard , the aim of the present study is to identify strategies and methods for creation and establishment of educational justice and barriers to its development . the present study is a descriptive - analytical research which its information is collected through reviewing books and articles and gathering data . in this paper , while explaining the importance and necessity of identifying the factors of educational justice , the most important obstacles facing the creation of educational equality in iran is mentioned . at the end , all factors and barriers affecting the creation of educational equity are organized under a comprehensive and obstacle pattern . the findings indicate that if educational equity is established in teaching - learning environment , fairness and equality in education and facilities , access to educational environment , motivation and hope to education and … will be more .